Analysis of Pregnancy Infection as a Risk Factor with the Event of Preeclampsia in Konawe Selatan District - Sarnian, Sarnian; Saafi, La Ode; Azizi Jayadipraja, Erwin; Risky, Sartini (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: The results of interviews with several midwives explained that preeclampsia patients were reported to be due to comorbidities, low hemoglobin, income, low education, and unhealthy lifestyles, obesity, age over 35 years with parity of one or parity of 4 or more children. . Therefore, the authors are interested in conducting research on risk factors with the incidence of preeclampsia. Method: Quantitative Research by designcase control studies. The population of all patients with preeclampsia was 174 cases with a sample of 120 respondents at the South Konawe District Health Center. The sampling technique used is simple random sampling. Result: The results of Chi Square analysis 56.26 > X2 Table 3.841 which means that there is a significant relationship between the infection variable and the incidence of preeclampsia. Conclusion: Infection risk factors for the incidence of preeclampsia in pregnant women with preeclampsia have a nine-fold risk.